Dada fait son cinéma - RĂILEANU, Petre (Studia Universitatis Babeș-Bolyai Dramatica, 2016)
Dada Makes a Fool of Itself. The theatre is part of the genetic code of Dadaism. The term “theatreˮ is understood here in all the senses of its semantic family: spectacle, representation, game, mise en scène and also interaction with the audience. The dialogue is essential, but also the stage design, the costumes and even the masks. The specificity of theatre is to be found in the fact that the signifier is linked to the word, but also – at the same level – to the stage design, the costumes, the movement, the music, the noises. Or, the great idea of Dada in the sphere of art is to abolish the “specific valueˮ of artistic means attributed by traditional aesthetics to each artistic genre, in other terms to mix many languages in a single object. The dada object includes the derisory, the heterogeneity, and associates to itself even the most unbelievable aspects.